Contemporary genetic structure and postglacial demographic history of the black scorpionfish, Scorpaena porcus, in the Mediterranean and the Black Seas. Issue 10 (14th May 2016) - Boissin, E.; Micu, D.; Janczyszyn‐Le Goff, M.; Neglia, V.; Bat, L.; Todorova, V.; Panayotova, M.; Kruschel, C.; Macic, V.; Milchakova, N.; Keskin, Ç.; Anastasopoulou, A.; et al.
Abstract: Understanding the distribution of genetic diversity in the light of past demographic events linked with climatic shifts will help to forecast evolutionary trajectories of ecosystems within the current context of climate change. In this study, mitochondrial sequences and microsatellite loci were analysed using traditional population genetic approaches together with Bayesian dating and the more recent approximate Bayesian computation scenario testing. The genetic structure and demographic history of a commercial fish, the black scorpionfish, Scorpaena porcus, was investigated throughout the Mediterranean and Black Seas. The results suggest that the species recently underwent population expansions, in both seas, likely concomitant with the warming period following the Last Glacial Maximum, 20 000 years ago. A weak contemporaneous genetic differentiation was identified between the Black Sea and the Mediterranean Sea. However, the genetic diversity was similar for populations of the two seas, suggesting a high number of colonizers entered the Black Sea during the interglacial period and/or the presence of a refugial population in the Black Sea during the glacial period. Finally, within seas, an east/west genetic differentiation in the Adriatic seems to prevail, whereas the Black Sea does not show any structured spatial genetic pattern of its population. Overall, these results suggest that the Black Sea is not that isolated from the Mediterranean, and both seas revealed similar evolutionary patterns related to climate change and changes in sea level.